2015
DOI: 10.1007/s10695-015-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective and antioxidant significance of selenium and α-tocopherol on lead acetate-induced toxicity of Nile Tilapia (Oreochromis niloticus)

Abstract: The kidney plays an important physiological function, maintaining the osmoregulation and electrolyte balance of Nile tilapia (Oreochromis niloticus). Selenium and α-tocopherol (α-toc) are potent antioxidants, which improve the aquaculture health. In this study, we tested the potential ability of selenium and α-toc to alleviate the oxidative stress in the kidney induced by lead toxicity. Two hundred and twenty-five O. niloticus were divided into five groups. The control group received a basal diet. Lead nephrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…MDA, GSH, GPx and T‐AOC are reported to be good biomarkers of Pb‐induced oxidative stress in aquatic animals (Hashish, Elgaml, El‐Murr & Khalil ). Consistent with these studies, oxidative stress in Nile tilapia after waterborne Pb exposure observed in this study was significantly reduced through dietary supplementation of L. plantarum CCFM8661, indicating that this probiotic can protect fish against Pb‐induced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…MDA, GSH, GPx and T‐AOC are reported to be good biomarkers of Pb‐induced oxidative stress in aquatic animals (Hashish, Elgaml, El‐Murr & Khalil ). Consistent with these studies, oxidative stress in Nile tilapia after waterborne Pb exposure observed in this study was significantly reduced through dietary supplementation of L. plantarum CCFM8661, indicating that this probiotic can protect fish against Pb‐induced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many studies have proved that proper nutritional supplementation can alleviate multiple stressors imposed by the environment, including heavy metals pollution (Hashish and Elgaml, 2015;Mezzomo et al, 2019;Ramos et al, 2018;Yu et al, 2016;).…”
Section: Introductionmentioning
confidence: 99%